"If it ain't broke, don't fi x it": internationalisation and the erosion of the positive hidden curriculum in Danish higher education1. (1st January 2013) - Blasco, Maribel; Tackney, Charles
Denmark is among the world's most competitive nations. It also has a strong tradition of citizenship-oriented higher education, promoted through the widespread Problem-Oriented Project Work (POPW) didactic approach. We argue that recent changes to this tradition have modifi ed the incentives embedded in the hidden curriculum, which made Danish higher education effective at producing graduates with analytical and personal abilities and dispositions, such as refl exivity, curiosity, collaboration and trust that are particularly suitable for today's globalised, knowledge-based economies. We illustrate this by drawing on examples of changes to an education programme at a Danish business school.